Oscillating solutions of a nonlinear fourth order ordinary differential equation - Amster, P. (2007)
We study the existence of periodic solutions for a nonlinear fourth order ordinary differential equation. Under suitable conditions we prove the existence of at least one solution of the problem applying coincidence degree theory and the method of upper and lower solutions. © 2006 Elsevier Inc. All rights reserved.